Are alternative livelihood projects effective at reducing local threats to specified elements of biodiversity and/or improving or maintaining the conservation status of those elements?: a systematic review protocol - Roe, D.; Day, M.; Booker, F.; Zhou, W; Allebone-Webb, S.; Hill, N.A.O; Wright, J; Rust, N; Sunderland, Terry C.H.; Redford, K.H.; Petrokofsky, G.; Kümpel, N.F. (Springer, 2014)
Alternative livelihood projects are used by a variety of organisations as a tool for achieving conservation results. Yet these interventions, including their objectives, vary a great deal, and there is no single accepted definition of what constitutes an alternative livelihood project. In addition, very little is known about what impacts, if any, alternative livelihoods projects have had on biodiversity conservation, as well as what determines the success or failure of these interventions. Reflecting this concern, a resolution was passed at the IUCN World Conservation Congress in 2012 calling for a critical review of the benefits to biodiversity of alternative livelihood projects. This systematic review is intended to contribute to this resolution.This protocol details the methodology for exploring the research question: Are alternative livelihood projects effective at reducing local threats to specified elements of biodiversity and/or improving or maintaining the conservation status of those elements? The aim of this proposed systematic review is to provide an overview for researchers, policy makers and practitioners of the current state of the evidence base. To undertake this, the systematic review will explore peer-reviewed research from the bibliographic databases SCOPUS, Web of Science, CAB Abstracts, AGRIS and AGRICOLA using search terms and Boolean search operators. The systematic review will also explore grey literature sources by conducting searches on Google, subject specific websites and institutional websites. Additionally, the review will use calls for papers and snowballing techniques to further identify literature. In order to identify relevant evidence, inclusion criteria will be used to screen the titles and abstracts of the captured literature. Data will be extracted from the final list of relevant documents by using a questionnaire established through literature review and a stakeholder workshop. The key output of this review will be a report on the state of the evidence, and, if the data permits, an estimate of the effectiveness of alternative livelihood interventions.